2022
DOI: 10.3390/agriculture12020308
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Resistant Starch Accumulation in Contrasting Wheat Genotypes Highlights the Lipid Metabolic Pathway Related to Resistant Starch Synthesis

Abstract: Resistant starch (RS) shows several health benefits. Enhancing the RS content of wheat is of major commercial importance. However, knowledge regarding the RS synthesis mechanism in wheat remains limited. In this study, the dynamic accumulation of RS during the filling process in two wheat (Triticum aestivum L.) genotypes with contrasting RS contents (H242, high RS content; H189, low RS content) were investigated. The results demonstrate that beyond 25 days after pollination (DAP), the RS content of H189 was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Of course, the changes in the starch physiochemical properties could not be excluded. Wang et al [24] also found that the RS content of a cultivar with a high RS content increased gradually with the development of grain filling but that of H189 (a low RS content cultivar) was relatively stable beyond 25 DAA. The comparison of different cultivars showed that RS639 had the highest total starch content, and RS683 had the lowest total starch content during kernel development.…”
Section: Accumulation Of Total Starch Amylose Amylopectin and Rs In W...mentioning
confidence: 97%
“…Of course, the changes in the starch physiochemical properties could not be excluded. Wang et al [24] also found that the RS content of a cultivar with a high RS content increased gradually with the development of grain filling but that of H189 (a low RS content cultivar) was relatively stable beyond 25 DAA. The comparison of different cultivars showed that RS639 had the highest total starch content, and RS683 had the lowest total starch content during kernel development.…”
Section: Accumulation Of Total Starch Amylose Amylopectin and Rs In W...mentioning
confidence: 97%
“…Pearson's correlation coefficient was used to calculate the correlation coefficients of FPKM of all transcripts among three replications for each sample. DESeq2 was used for differential expression analysis based on count value, and clustered profiles of genes with a p value ≤ 0.05 and |log 2 (fold-change)| ≥ 1 were considered differentially expressed [70]. STEM was conducted to classify the identified DEG expression patterns.…”
Section: Total Rna Extraction Library Construction Sequencing and Bio...mentioning
confidence: 99%
“…Primers (Table S3) were designed using Primer v5 software (Premier Biosoft International, San Francisco, CA, USA), and ubiquitin (UBQ5) was used as an internal control. The experimental operating system used for RT-qPCR was described in our previous studies [70,72]. The data were processed according to the Ct (2 −∆∆Ct ) method.…”
Section: Rt-qpcr For Rna-seq Validationmentioning
confidence: 99%